2020
DOI: 10.1186/s12917-020-02457-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of p53 and pp53 Ser392 in canine hemangiomas and hemangiosarcomas located in the skin

Abstract: Background: p53 protein is essential for the regulation of cell proliferation. Aberrant accumulation of it usually occurs in cutaneous malignancies. Mutant p53 is detected by immunohistochemistry because it is more stable than the wild-type p53. However, post-translational modifications of p53 in response to ultraviolet radiation are important mechanisms of wild-type p53 stabilization, leading to positive staining in the absence of mutation. The aims were: 1) to analyze the immunohistochemical expression of p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 49 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…However, it is important to highlight that TP53 mutations are important and frequently found in several cancer subtypes. García-Iglesias et al [ 20 ] found a high expression of the mutated TP53 gene associated with high Ki-67 proliferative activity in 25 dogs with cutaneous HSA, suggesting the association of this gene mutation with neoplastic development. Both studies included patients with dermal and hypodermic HSAs.…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to highlight that TP53 mutations are important and frequently found in several cancer subtypes. García-Iglesias et al [ 20 ] found a high expression of the mutated TP53 gene associated with high Ki-67 proliferative activity in 25 dogs with cutaneous HSA, suggesting the association of this gene mutation with neoplastic development. Both studies included patients with dermal and hypodermic HSAs.…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
“…Several studies have identified immunohistochemical markers for the diagnosis of HSA, including the Willebrand factor (FVIII), VEGF, bFGF, and claudin-5 [ 22 , 31 , 35 , 36 ]. In addition, García-Iglesias et al (2020) [ 20 ] demonstrated that CD117 immunoexpression (KIT) and Ki-67 index could be useful in differentiating between cutaneous HSA and hemangioma.…”
Section: Diagnosis and Stagingmentioning
confidence: 99%
“…In the same study, TP53 mutations were detected in 35% of cutaneous tumors (12 out of 34). Other investigations have also reported frequent TP53 mutations in human angiosarcomas [7–9] . Collectively, these genetic studies strongly suggest that the PI3K, MAPK, and TP53 pathways play an important role in the development of angiosarcoma.…”
Section: Discussionmentioning
confidence: 52%
“…The rarity of angiosarcoma makes large genomic studies to identify pathologic driver mutations almost impossible. Nonetheless, recent sequencing studies have implicated the PI3K, MAPK, and TP53 pathways as key oncogenic mechanisms driving the development of angiosarcoma [6–10] . In 2019, Cao et al [21] detected somatic alterations in PIK3CA and PIK3R1 (the 85 kDa regulatory subunit of PI3K) in the tumor specimen of a 51-year-old female patient with primary splenic angiosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…García–Iglesias et al. found that p53 and phosphorylated p53 serine were highly expressed in angiosarcoma [62] . Kiyohara et al.…”
Section: Discussionmentioning
confidence: 99%